Pemanfaatan Media Audio Visual Dalam Peningkatan Hasil Belajar Pendidikan Agama Islam Pada Siswa Sekolah Dasar Negeri (Sdn) 1 Semampir Jepon Blora Tahun 2015 - Rusuli, Rusuli (2016)
The purpose of this study is to describe the purpose of teachers in the use of audio visual media on the subjects of PAI, the use of audio visual media in improving student learning outcomes in subjects PAI and student learning outcomes after the teacher uses audio-visual media on the subjects PAI at SDN 1 Semampir Jepon Blora 2015. this research type of field research with qualitative descriptive analysis of the feneomena that occur in the field. Data were collected by interview, observation and documentation. The results showed that the first, the purpose of the teacher uses audio-visual media on the subjects PAI at SDN 1 Semampir Jepon Blora are in accordance with the theory of the objectives of the audio-visual media as described by Mulyono Abdur Rahman in his book Education for Children learning disabilities are teachers able to convey the concept , ideas and experiences captured by the sense of viewing and hearing. The learning conditions are also able to encourage motivation to learn, clarify and simplify the complex and abstract concepts become more simple, concrete and easily understood. Second, the use of audio-visual media in improving learning outcomes in subjects PAI role as it should, that evoke the spirit of the students, and facilitate teachers in conveying the message or lesson. The use of audio-visual media in subjects PAI at SDN 1 Semampir Jepon Blora has been scheduled, namely a maximum of three times in the semester the teacher uses audio-visual media. Before using media, teachers have held the preparation, implementation, follow-up activities or evaluation. Third, the learning outcomes of students after a teacher uses audio-visual media on subjects PAI, then the teacher to conduct an evaluation of learning outcomes is a process for determining the value of student learning through assessment and measurement of learning outcomes. The goal is to determine student progress within a certain period of time learning process. The results of students of class IV, V SDN 1 Semampir Jepon Blora after the teacher uses audio-visual media on subjects PAI very well at all, the average student got a lot of good learning results with a frequency of 70-85 compared with the value before the teacher utilizing audio madia visual. Thus the use of audio-visual media on subjects PAI very useful for teachers and students, as teachers easier to explain materials about PAI on prayer and taharah and make improving student learning outcomes.